(untitled) - Suzuki, D. T. (New York, 1960)
The book marked a turning point in Zen literature in its critical reevaluation of the enlightenment experience, which the author believes has often been emphasized at the expense of other important aspects of Zen training. In addition, Zen Training goes beyond the first flashes of enlightenment to explore how one lives as well as trains in Zen. The author also draws many significant parallels between Zen and Western philosophy and psychology, comparing traditional Zen concepts with the theories of being and cognition of such thinkers as Heidegger and Husserl.
Keywords: Zen Buddhism,Psychoanalysis and religion